The Genesis of Literary Postmodernism: Ukrainian / Western Models (Literatures of the World: Poetics, Mentality and Spirituality, 2014)
In the article is researched the genesis of literary postmodernism. Chief attention is paid to researching its western and Ukrainian variants, the analysis views of modern literary critics about the phenomenon of literary postmodernism in contemporary literature. The author discloses the main characteristics and neo-baroque features of postmodern literature.
Keywords: baroque; genesis; literary postmodernism; neo-baroque; modern literary process